1978
DOI: 10.1111/j.1469-8986.1978.tb01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance and Human Attention Under Conditions of Methylphenidate and Secobarbital Intoxication: An Assessment Using Brain Potentials

Abstract: Performance is known to fall‐off with the time on a vigilance task. Treatment with methylphenidate attenuates this decrement while treatment with secobarbital enhances it. This experiment was designed to test whether this performance decrement and the drug effects on it are associated with changes in selective attention or in general state (i.e. motivation, alertness, or arousal). Subjects were treated with either 10 mg of methylphenidate, 100 mg of secobarbital, or a placebo in a double‐blind cross‐over desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

1979
1979
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 25 publications
2
13
0
4
Order By: Relevance
“…In studies where there was no reduction in P3B due to fatigue or boredom over the placebo day, stimulants had no effect on P3B [10][11][12][13]. The correlation between self-reported tired scale and P3B reduction on the placebo day in the present study suggest that the decline on the placebo day was due to fatigue.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…In studies where there was no reduction in P3B due to fatigue or boredom over the placebo day, stimulants had no effect on P3B [10][11][12][13]. The correlation between self-reported tired scale and P3B reduction on the placebo day in the present study suggest that the decline on the placebo day was due to fatigue.…”
supporting
confidence: 58%
“…Other stimulants such as amphetamine reduce the disruptive effects of repetition, boredom, fatigue and sleep deprivation on task performance [1][2][3][4][5][6][7][8][9][10][11][12][13]. Cocaine has also been reported to reverse the effects of fatigue and sleep deprivation [14][15][16], While cocaine has been shown to improve task performance in nonfatigued subjects [17][18][19], it has also been reported to be without any effects on similar tasks [19,20], Likewise, there is inconsistency in reports focusing on the effects of intravenous and oral doses of cocaine-altered event-related potentials (ERPs) elicited during cognitive tasks in nonfatigued subjects [21,22], Cocaine reduced the P3B component of auditory ERP elicited by the target tone in an auditory oddball tasks [21], Cocaine increased N100 amplitude and the contingent negative variation (CNV) elicited by the warn ing stimulus, but did not alter P3B amplitude elicited by the target stimuli in a continous performance task [22], It was thought that the lack of consistency might be due to the fact that most of these studies [18][19][20][21][22] had used individuals who use cocaine intermittently (once a week or less).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of effect was explained in terms of a ceiling effect, the tasks were very easy. Two studies reported on the decrement: Hink et al (1978) reported no effect of methylphenidate on d', but this is not surprising. There was no decrement in the placebo condition, and the authors used a task in which the vigil was interrupted every 5 min.…”
Section: Inspection Ofmentioning
confidence: 69%
“…Details of procedures and results are presented in the Appendix. Experiments using amphetamine have rarely been carried out during the last decade, whereas studies employing caffeine and nicotine are practically confined to the last decade which is somewhat surprising for the two Hink et al (1978) 15) Coons et al (1981) 16) Aman et al (1984) 17) Strauss et al (1984) Part 3: Caffeine 18) Baker & Theologus (1972) 19) Keister & McLaughlin (1972) 20) Clubley et al (1979) 21) Rapoport et al …”
Section: Methodsmentioning
confidence: 94%
“…This was in terpreted as suggestive of an attention-enhancing effect of this drug. In a similar investigation of secobarbital and methylphenidate, Hink et al [1978] could not find an effect on the auditory 'attention effect'. The suppres sion of the Nl peak to both attended and inattended stimuli was viewed as a change of overall responsiveness of the brain rather than a change in selective attention.…”
Section: Discussionmentioning
confidence: 94%